Proposal to expand the pumping system for treatment and recirculation of underground water in a mining operation - (:unkn) unknown (LACCEI (Latin American and Caribbean Consortium of Engineering Institutions), 2024)
This work presents a proposal for the expansion of a water treatment system inside an underground mine, and thus optimize the water resource present in the mining operation. For this purpose, the design parameters of an existing two-stage pumping system ...
Keywords: Aguas subterráneas; Minería